Phosphate-Solubilizing Bacteria with Solid Carrier Material in The Cultivation of Sweet Corn - Eko Hary Pudjiwati; Nur Indah Mansyur; Esra Margaretha Marpaung; Muhammad Adiwena (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2026)
The limited availability of fertile land is a strong reason to utilize marginal land. Marginal land has potential for agricultural development because it has relatively high total phosphorus, but this phosphorus is in a form that is not available to plants. The use of phosphate-solubilizing bacteria (PSB) can be an alternative to change this form. The effectiveness of PSB activity in altering this form can be enhanced through carriers that are able to maintain their viability and activity in the soil. This study investigates the use of marginal land treated with phosphate solubilizing bacteria (PSB) incorporated with carrier materials to addressing the demand for sweet corn. PSB application followed a Randomized Block Design (RBD) involving the treatments as follows: control (T0), 150 kg Super Phosphate-36 (SP-36) per hectare (T1), PSB B5(6) + shrimp shells + 75 kg SP-36 per hectare (T2), PSB B1(17) + shrimp shells + 75 kg SP-36 per hectare (T3), PSB B5(6) + husk charcoal + 75 kg SP-36 per hectare (T4) and PSB B1(17) + husk charcoal + 75 kg SP-36 per hectare (T5). The results yield the optimum outcome associated with T2 by plant height (±70.25 cm), number of leaves (±8.97 pieces) and roots (±41 cm), root length (±31.10 cm) and volume (±14.05 ml), plant fresh (±53.72 gr) and dry weight (±28.01 gr), cob weight with husk (± 23.68) and without husk (±14.67 gr), cob length with husk (±12.88 cm) and without husk (±7.38 cm), cob diameter with husk (±22.76 cm) and without husk (±16.67 cm). T2 can reduce the use of inorganic phosphorus fertilizer up to 50% and increase production by approximately 7 times better than control.